2017
DOI: 10.2147/ceor.s130334
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to disease-modifying therapies and its impact on relapse, health resource utilization, and costs among patients with multiple sclerosis

Abstract: Purpose To evaluate adherence to disease-modifying therapies (DMTs) among patients with multiple sclerosis (MS) initiating oral and injectable DMTs, and to estimate the impact of adherence on relapse, health resource utilization, and medical costs. Patients and methods Commercially insured MS patients (aged 18–65 years, two or more MS diagnoses, one or more DMT claims) with continuous eligibility 12 months before and after the first DMT claim date (index date) and no DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 47 publications
5
129
3
1
Order By: Relevance
“…Nevertheless, evidence from privately insured patients suggests that nonadherence to MS DMTs is associated with an increased risk of relapse and health resource utilization. 35,36 Future research should examine whether similar findings are identified in the Medicare population.…”
Section: Pdc Indicates Proportion Of Days Coveredmentioning
confidence: 81%
“…Nevertheless, evidence from privately insured patients suggests that nonadherence to MS DMTs is associated with an increased risk of relapse and health resource utilization. 35,36 Future research should examine whether similar findings are identified in the Medicare population.…”
Section: Pdc Indicates Proportion Of Days Coveredmentioning
confidence: 81%
“…Despite the risks, there are also considerable benefits to open communication regarding MS disease progression. Slowing disease progression is the primary aim of HCPs treating MS [27]; however, real-world studies show treatment discontinuation and non-adherence rates of around 30% [28][29][30][31]. Indeed, the actual rates of non-adherence may be even higher than reported [32].…”
Section: Benefits Of Open Communication About Disease Progressionmentioning
confidence: 99%
“…In addition, research has found that adherence varies widely across studies, with estimates ranging from 47% to 93% 8,[11][12][13][14] . Adherence is critically important given that it is associated with reduced relapse rates [14][15][16] , improved health-related quality of life 17 , better physical outcomes 18 , and lower healthcare utilization and costs 15,19,20 .…”
Section: Introductionmentioning
confidence: 99%